Conflict Management Strategies on the Learning Process of Nursing Undergraduate Students During the Covid-19 Pandemic - Nita Sri Wahyuningsih; Dina Susanti (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: The learning process is an interaction of information exchange that occurs between lecturers and students supported by the media and methods used. The interaction that occurs will trigger the emergence of conflict so that conflict management is needed as a self-defense mechanism so that learning objectives can be achieved. Moreover, interactions that take place only online due to the situation of increasing the number of Covid-19 cases, based on the new government policy with restrictions on community activities (PPKM) where the teaching and learning process is 100% carried out online. conflict management strategy as independent variable and learning process as dependent variable Objective: This study aims to knowing the relationship of conflict management of Bachelor of Nursing students in the implementation of the learning process. Methods: This study used a descriptive correlation design with a cross sectional approach. The sample used in this study was 267 students. research instrument in the form of a questionnaire given via google form then analyzed with spss. Results: The results of this study indicate that there is a significant relationship between conflict management and the implementation of the learning process and the most dominant collaborative conflict management is carried out by students during the learning process. Conclusion: This result of this study stated that the learning process runs smoothly, students use conflict management strategies to overcome them. The lecturers suggested to to direct how students can manage improve the learning process through conflict management among the students.